2015
DOI: 10.1016/j.promfg.2015.07.106
|View full text |Cite
|
Sign up to set email alerts
|

Failure Mode, Effects and Criticality Analysis (FMECA) for Medical Devices: Does Standardization Foster Improvements in the Practice?

Abstract: Risk analysis techniques received increasing attention in the health care sector in the last 30 years. These techniques are diffused\ud for health care processes, and less for devices. In fact, risk management for medical devices was introduced only recently (ISO\ud 14971 in 2000 and GHTF/SG3/N15R8 in 2005) [1,2]. The goal of this study is twofold. First, we aim at evaluating the state of\ud the art of the diffusion of standards for the risk assessment of medical devices (with a focus on FMECA). Second, we eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…It is a systematic procedure to identify potential failure modes, cause, and effect on system performance. Given the prominent efficiency and effect on identifying failure modes and root causes of undesired consequences, this effective approach has widely been applied to various industries such as aircraft equipment [38], medicinal devices [39], and shipbuilding industry [23].…”
Section: Fmecamentioning
confidence: 99%
“…It is a systematic procedure to identify potential failure modes, cause, and effect on system performance. Given the prominent efficiency and effect on identifying failure modes and root causes of undesired consequences, this effective approach has widely been applied to various industries such as aircraft equipment [38], medicinal devices [39], and shipbuilding industry [23].…”
Section: Fmecamentioning
confidence: 99%
“…Particularly FMECA (a logical extension of FMEA -Failure Mode Effect Analysis) and HFMEA ™ -Healthcare Failure Mode and Effect Analysis) are among the most popular proactive methods in health care [10]. FMECA methodolgy is mainly used in manufacturing [13] and it has been recently demonstrated that is a valid risk assessment tool to analyse process involving medical devices [22], risk assessment of medical device [11,23] also in home ventilation [10]. On the contrary, HFMEA ™ is more oriented to the analysis of clinical processes (such as nursing and other clinical aspects) [4,10,21].…”
Section: Fmecamentioning
confidence: 99%
“…Despite encouraging results in the 3D bioprinting technology, there is still a gap between the research applications and their clinical use due to several issues that need to be addressed [15]. Optimizing and standardizing this process in the research phase is pivotal for fostering its proper and faster translation into clinics [16]. To the best of our knowledge, no studies have described, in a step-by-step fashion, the sequential phases of a bioprinting process with its respective failure modes and mitigation actions.…”
Section: Introductionmentioning
confidence: 99%